Immune diversity sheds light on missing variation in worldwide genetic diversity panels - Abi-Rached, Laurent (PLoS One, 2018)
Defining worldwide human genetic variation is a critical step to reveal how genome plasticity contributes to disease. Yet, there is currently no metric to assess the representativeness and completeness of current and widely used data on genetic variation. We show here that Human Leukocyte Antigen (HLA) genes can serve as such metric as they are both the most polymorphic and the most studied genetic system. As a test case, we investigated the 1,000 Genomes Project panel. Using high-accuracy in silico HLA typing, we find that over 20% of the common HLA variants and over 70% of the rare HLA variants are missing in this reference panel for worldwide genetic variation, due to undersampling and incomplete geographical coverage, in particular in Oceania and West Asia. Because common and rare variants both contribute to disease, this study thus illustrates how HLA diversity can detect and help fix incomplete sampling and hence accelerate efforts to draw a comprehensive overview of the genetic variation that is relevant to health and disease.